2022
DOI: 10.14366/usg.21143
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced voiding ultrasonography to detect intrarenal reflux in children: comparison with 99mTc-DMSA renal scans

Abstract: To evaluate the diagnostic performance of contrast-enhanced voiding ultrasonography (CeVUS) detecting intrarenal reflux (IRR) and propose the correlation between sites of IRR detected by CeVUS and photon defect sites in acute 99mTc-DMSA renal scan in pediatric patients. Methods: Fifty-four kidneys from 27 patients (20 males and 7 females; mean age, 5.6±4.1 months) who underwent CeVUS and acute DMSA renal scan for recurrent urinary tract infection (UTI) or pyelonephritis were included. Pediatric experts compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…There is currently only insufficient literature regarding the periprocedural application of an antibiotic for ceVUS. Some individual studies were performed without the administration of antibiotics [38] or with a single administration on the day of the examination [39]. In comparison, administration of an antibiotic the day before, the day of, and the day after VCUG is recommended [40].…”
Section: Alternative Method: Cevusmentioning
confidence: 99%
See 3 more Smart Citations
“…There is currently only insufficient literature regarding the periprocedural application of an antibiotic for ceVUS. Some individual studies were performed without the administration of antibiotics [38] or with a single administration on the day of the examination [39]. In comparison, administration of an antibiotic the day before, the day of, and the day after VCUG is recommended [40].…”
Section: Alternative Method: Cevusmentioning
confidence: 99%
“…However, this is being reexamined in new studies from the year 2023 [4,41]. In the case of additional obstructive diseases of the urinary tract, antibiotic prophylaxis should be implemented [38].…”
Section: Alternative Method: Cevusmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the diagnosis of VUR, as well as the diagnosis of IRR, is possible without radiation burden by using the ceVUS method, especially with the second generation of contrast media [9,10,55,[62][63][64][65][66]. The use of ceVUS opened new possibilities for the diagnosis of IRR, showing that the incidence of IRR appeared in a range between 11.9 and 61.5% out of all diagnosed VURs [9,10,55,[64][65][66]. The study by Simičić A. et al showed that 100% of VURs grade IV and V and 83.8% of VURs grade III had IRR.…”
Section: The Diagnostic Methods For the Detection Of Irr: Cevusmentioning
confidence: 99%